2020
DOI: 10.5500/wjt.v10.i7.206
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation in simultaneous pancreas kidney transplantation - On what basis?

Abstract: BACKGROUND Despite technical refinements, early pancreas graft loss due to thrombosis continues to occur. Conventional coagulation tests (CCT) do not detect hypercoagulability and hence the hypercoagulable state due to diabetes is left untreated. Thromboelastogram (TEG) is an in-vitro diagnostic test which is used in liver transplantation, and in various intensive care settings to guide anticoagulation. TEG is better than CCT because it is dynamic and provides a global h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Regarding the use of blood products, the studies revealed different results. TEG parameters reduced the usage of blood products [156][157][158]; however, in comparison to other conventional tests or clinician-directed transfusion system, no differences were observed except for Sujka et al who found TEG-directed transfusion system reduced only FFP use between other blood products [150,159,160]. Coakley et al investigated both TEG and ROTEM parameters and found that ROTEM improved clinicians' decisions compared to TEG usage [161].…”
Section: Transplantmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the use of blood products, the studies revealed different results. TEG parameters reduced the usage of blood products [156][157][158]; however, in comparison to other conventional tests or clinician-directed transfusion system, no differences were observed except for Sujka et al who found TEG-directed transfusion system reduced only FFP use between other blood products [150,159,160]. Coakley et al investigated both TEG and ROTEM parameters and found that ROTEM improved clinicians' decisions compared to TEG usage [161].…”
Section: Transplantmentioning
confidence: 99%
“…This controversy was seen also in the prediction of liver cirrhosis [ 148 , 163 ]. TEG’s usage was not associated with mortality or survival rates [ 156 , 160 ]. On the other hand, it decreased hospital stay length and reoperation needs [ 147 , 160 ] (Table 8 ).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Donor factors (including age, weight, and gender) and perioperative factors (cold ischemic time, warm ischemic time, preservation solution, exocrine drainage, and arterial reconstruction) are known to affect thrombosis risk [ 103 , 129 , 135 ]. There is also evidence in retrospective studies that anticoagulation does prevent allograft thrombosis in these patients, but this must be balanced with the risk of rebleeding and risk of repeat exploratory laparotomy caused by excess anticoagulation [ 129 , 131 , 132 , 135 , 136 , 137 , 138 , 139 , 140 ]. For each case, an assessment of thrombotic risk should be made based on donor factors, recipient factors and perioperative factors, and a degree of anticoagulation should be begun commensurate with this calculated risk.…”
Section: Anti-coagulationmentioning
confidence: 99%
“…TEG allows rapid, real-time assessment of both clot formation as well as fibrinolysis making it ideal for titration of anticoagulation in the perioperative period [ 141 , 142 ]. In a retrospective study, Gopal et al demonstrated that there was reduced bleeding (18% vs. 45%, p = 0.05) and reduced length of hospital stay (18 vs. 31 days, p = 0.03) in anticoagulation titrated using TEG vs. standard coagulation tests (prothrombin time and activated partial thromboplastin time), respectively [ 137 ]. Regular preoperative monitoring of platelet function through the collagen-epinephrine closure time (Col/Epi) and collagen-ADP assay (Col/ADP) could be beneficial, but more work is needed to evaluate their clinical value.…”
Section: Anti-coagulationmentioning
confidence: 99%